PENGARUH KEMUDAHAN, RISIKO, MANFAAT DAN KENYAMANAN TERHADAP MINAT MENGGUNAKAN LAYANAN MOBILE BANKING - Keyka Finannafi'ah; Banu Witono (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The research entitled The Effect of Ease, Risk, Benefit, and Convenience on Interest in using Mobile Banking aims to analyze and determine the effect of public interest in Sragen Regency in using Mobile Banking. The method used in this study is a comparative causal type with a quantitative approach. The population in this research is the people in Sragen Regency. While the sampling technique in this study used purposive sampling. So from the calculation result, the sample of this research is 100 samples from the total population in Sragen Regency. This research was processed using the Statistical Package for Social Science (SPSS) version 25 application. The results showed that convenience, risk, benefit and convenience significantly influenced the interest in using Mobile Banking in the community in Sragen Regency.